MAPPING SUPPLY CHAIN STRATEGY ON SWEET POTATO COMMODITY IN MEDAN CITY - Akbar Habib; Dian Retno Intan; Wildani Lubis (Jurnal Agrisep)
The concept of supply chain management (SCM) has been widely used but is limited to industrial products, while in agriculture, especially fresh products, it has received little attention. In fact, when viewed from the characteristics of the product, agri-fresh supply chain management (FSCM) is very necessary. This study was carried out in addition to identifying the supply chain of sweet potato which is an important food crop in North Sumatra as well as being an additional reference in research that focuses on sweet potato commodities.This research was conducted in the area of Sei Beras Sekata, Sunggal, Deli Serdang. Respondents are actors in the supply chain, starting from farmers to consumers. The sample is determined through the snowball sampling technique because there is no sample frame. There were 29 informants in this study consisting of farmers, collectors, agents, traders and consumers.The research showed that there are three sweet potato supply chain lines, involving four marketing agencies. The first channel is a supply chain channel without intermediaries, meaning that farmers sell directly to consumers. The second channel is a channel with one intermediary, where farmers first sell sweet potatoes to retailers and then retailers sell to consumers. The third channel is the channel that has the longest chain, which involves collectors, agents, and retailers.